A Scoping Review of the Conceptual Differentiation of Technology for Healthy Aging. (29th July 2021) - Kim, Hansuk; Kelly, Sarah; Lafortune, Louise; Brayne, Carol
Abstract: Background and Objectives: With the emergence of healthy aging as a key societal issue in recent decades, technology has often been proposed as a solution to the challenges faced by aging societies. From a public health perspective, however, aging-related technologies have been inconsistently conceptualized and ill-defined. By examining how relevant concepts in "technology for aging" have been developed to date, we hope to identify gaps and begin clarifying the topic. Research Design and Methods: We conducted a scoping review according to PRISMA-ScR, drawing on PubMed and Embase. We selected articles that directly reported concepts of technology for aging, or from which such concepts could be inferred. Results: We identified 43 articles, most of which were narrative reviews ( n = 31). Concepts of technology for aging were presented in diverse ways with some overlap. Most studies provided some terminology ( n = 36), but with little conceptual uniformity. Conceptual discourse was often focused on the aging agenda; while technological aspects were poorly defined. A conceptual framework from a public health perspective was derived from 8 articles—it showed that technology strategies do not take a population approach. Discussion and Implications: While the potential of "technology for aging" is vast, its real capacity to deliver a desirable life for older people remains underdeveloped. Clearer concepts and realistic goals at population level are lacking. Efficient investment must be made throughout the social system, and technology needs to be integrated via macro-level practices.